Organizational Citizenship Behavior (OCB) Influence on Employee Performance in Hospital - Rahman, Fauzie; Arifin, Syamsul; Wibowo, Yoga Putra; Riana; Erlyan, Nekai (South Eastern European Journal of Public Health, 2024)
Organizational citizenship behavior (OCB) holds a fundamental position in influencing the efficacy of employee performance evaluations. Employing a mixed methods research design, specifically a commentary approach, this study encompasses all employees across various units of Hospital X in Banjarbaru City. Through purposive sampling, a non-probability method, 32 respondents were selected as samples. Findings reveal dimension scores: Altruism at 486, Courtesy at 668, Conscientiousness at 569, Sportmanship at 584, and Civic Virtue at 603. The study concludes that employee performance at X Hospital in Banjarbaru City is commendable across dimensions of Courtesy, Civic Virtue, Sportmanship, Conscientiousness, and Altruism.